Active Trigger Points in the Cervical Musculature Determine the Altered Activation of Superficial Neck and Extensor Muscles in Women With Migraine. Issue 3 (March 2017) - Florencio, Lidiane L.; Ferracini, Gabriela N.; Chaves, Thais C.; Palacios-Ceña, María; Ordás-Bandera, Carlos; Speciali, José G.; Falla, Deborah; Grossi, Débora B.; Fernández-de-las-Peñas, César
Abstract : Objective: Previous studies have demonstrated the presence of active trigger points (TrPs) in women with migraine reproducing their headache attacks. No study has investigated whether these TrPs can alter cervical muscle function in migraine. Our objective was to analyze differences in the activation of superficial neck flexor and extensor muscles in women with migraine considering the presence of active TrPs in the splenius capitis (SC), the upper trapezius (UT), and the sternocleidomastoid (SCM) muscles. Methods: Surface electromyography (EMG) was recorded from the superficial flexors (SCM and anterior scalene) and the extensor (SC, UT) muscles bilaterally as participants performed a staged task of cranio-cervical flexion (CCF; 5 contractions representing a progressive increase in CCF range of motion) in 70 women with migraine. They were stratified according to the presence or the absence of active TrPs in the SCM, the SC, or the UT musculature. A comparison of EMG normalized root mean square (RMS) values was conducted with a 2×5 analysis of covariance with the task level as the within-subject variable, group stratified by active TrPs as the between-subjects variable and the presence of neck pain as a covariable. Results: All patients exhibited active TrPs in their cervical muscles, which reproduced their migraine. Women with migraine exhibiting active TrPs in the SCM ( P <0.01), the UT ( P <0.05), or the SC ( P <0.05) muscles had lower normalized RMS values of their superficial neck flexors than those without active TrPs in the same muscles. In addition, individuals exhibiting active TrPs in the SC and the UT (both, P <0.05) muscles had higher normalized RMS values in the SC muscle than those without active TrPs in the same muscles. Conclusions: The presence of active TrPs in the cervical musculature determines an altered activation of superficial neck and extensor muscles during low-load, isometric CCF contractions in women with migraine.